Análise viscoelástica de pavimentos asfálticos pelo método dos elementos finitos - Portela, Enson de Lima (2008)
This paper discusses the consideration of the viscoelastic behavior of asphalt mixtures in the stress analysis of flexible pavements and presents an incremental algorithm, based on the Finite Element Method, for the analysis of viscoelastic solids. The algorithm uses the integral approach where the stress is written as a convolution integral and the rexalation modulus is represented by a Prony series. The semi-analytic solution of this convolution integral leads to an efficient incremental algorithm where the variables at the current time depend only on the values of the previous step. The algorithm is validated by using a well-known example whose analytical solution can be found by the elastic-viscoelastic correspondence principle and is applied to assess the influence of the viscoelastic behavior in the mechanical response of a flexible pavement.